(untitled) (Eurasian Journal of Engineering and Technology, 2022)
On a global scale, 140 countries produce more than 250 million hectoliters of wine with a total vineyard area of 7.6 million hectares. Spain, China, France rank first, Uzbekistan thirteenth in the world in terms of vineyard area, cultivated on 73 thousand hectares, of which 10 thousand hectares are considered wine grape varieties.